2013
DOI: 10.3892/mmr.2013.1535
|View full text |Cite
|
Sign up to set email alerts
|

Gastrodin ameliorates Parkinson’s disease by downregulating connexin 43

Abstract: Abstract. Gastrodin, the predominant constituent of a Chinese herbal medicine, has been utilized in the prevention of Parkinson's disease (PD); however, its mechanism of action remains unknown. Astrocytes are involved in PD and are proposed to be coupled with gap junction connexin 43 (Cx43). To evaluate the effects of gastrodin on PD, the effect of gastrodin on Cx43 in astrocytes and in a PD model were observed. Different doses of gastrodin were added to the astrocyte culture medium or injected into the roteno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 32 publications
0
24
0
Order By: Relevance
“…Some studies have shown that phosphorylated gap junction protein connexin 43 is selectively enhanced in the basal ganglia regions, which contain dopamine neurons or their terminal areas (striatum) [30,31]. PD is ameliorated by Gastrodin by downregulating connexin 43 [32]. …”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that phosphorylated gap junction protein connexin 43 is selectively enhanced in the basal ganglia regions, which contain dopamine neurons or their terminal areas (striatum) [30,31]. PD is ameliorated by Gastrodin by downregulating connexin 43 [32]. …”
Section: Discussionmentioning
confidence: 99%
“…An LSM710 confocal microscope (Carl Zeiss) was used for imaging. Sarcomere length was analyzed using ImageJ (version 1.46r, Wayne Rasband, NIH) (Wang et al., 2013, Nance et al., 2015). …”
Section: Methodsmentioning
confidence: 99%
“…In addition, GAS significantly attenuates the levels of neurotoxic proinflammatory mediators and proinflammatory cytokines by inhibiting the nuclear factor-κB signaling pathway and phosphorylation of mitogen-activated protein kinases (MAPKs) in lipopolysaccharide-stimulated microglial cells (13). GAS also ameliorates Parkinson's disease by downregulating connexin 43 (14), and improves anxiety-like behaviors by decreasing the levels of interleukin (IL)-1β and inhibiting p38 MAPK phosphorylation in the hippocampus of a rat model of post-traumatic stress disorder (15). These findings indicated that GAS may exert beneficial effects on diseases of the central nervous system.…”
Section: Introductionmentioning
confidence: 99%